Missed Carotid Artery Cannulation: A Line Crossed and Lessons Learnt. Issue 6 (November 2014) - Ho, L.; Spanger, M.; Hayward, P.; Mcnicol, L.; Weinberg, L.
We report a case of an infusion of intra-aortic propofol after the missed inadvertent placement of a centra venous catheter into the right common carotid artery. Radiological imaging revealed bilateral ischaemic infarct in the posterior fossa and right cerebral artery territories consistent with an embolic source. The potential cause of the neurological injuries sustained in this case are explored. Discussion focuses on the sequelae, managemen and prevention of an iatrogenic carotid artery injury from a central venous catheter insertion. Finally, we propose an algorithm for management of iatrogenic carotid artery cannulation.